A novel locus for autosomal dominant non-syndromic hearing loss, DFNA31, maps to chromosome 6p21.3. Issue 1 (16th January 2004) - Snoeckx, R L; Kremer, H; Ensink, R J H; Flothmann, K; de Brouwer, A; Smith, R J H; Cremers, C W R J; Van Camp, G
Abstract : Background: Non-syndromic hearing loss is the most genetically heterogeneous trait known in humans. To date, 51 loci for autosomal dominant non-syndromic sensorineural hearing loss (NSSHL) have been identified by linkage analysis. Objective: To investigate the genes involved in a Dutch family with NSSHL. Methods: Linkage analysis in a large Dutch pedigree with progressive bilateral loss of the mid and high frequencies, in which a novel dominant locus for postlingual NSSHL (DFNA31) has been identified. Results: DFNA31 was found to be located in a 7.5 cM region of chromosome 6p21.3 between D6S276 (telomeric) and D6S273 (centromeric), with a maximum two point LOD score of 5.99 for D6S1624. DNA sequencing of coding regions and exon/intron boundaries of two candidate genes ( POU5F1, GABBR1 ) in this interval did not reveal disease causing mutations. Conclusions: Haplotype analysis indicated that the genetic defect in this family does not overlap the DFNA13 and DFNA21 regions that are also located on 6p. Identification of the disease gene will be of major importance in understanding the pathophysiology of hearing impairment.